PARTISIPASI UMAT BERIMAN SEBAGAI PENGURUS DEWAN PASTORAL PAROKI PERIODE 2015-2018 DI PAROKI REGINA PACIS MAGETAN - Bryan Michael Wijaya; Don Bosco Karnan Ardjianto (Lembaga Penelitian STKIP Widya Yuwana, 2018)
To continue Christ's missions, the Church always need participation of lay people as members of Parish Council. In fact, most of them have many reasons to refuse participating as Parish Council's members, although sacrament of baptism urges them to participate in threefold of Christ and the Church's mission. Therefore, it could be stated some statements of the problems: What is the meaning of the participation of the faithful in threefold of Christ? What is the meaning of Pastoral Parish Council (PPC)? How were the faithful's participation as the Pastoral Parish Council in Regina Pacis Parish of Magetan in 2015-2018? This study attempts to describe the participation of the faithful in threefold of Christ, to explain the Pastoral Parish Council, and then to analyze of the faithful's participation as the Pastoral Parish Council in Regina Pacis Parish of Magetan in 2015-2018. This study applied the qualitative research method, the respondents of the research were ten members of PPC. While to collect data, this study conducted structured interviews method. Conclusions of this research are: first, all of the community understand the meaning the faithful, the laity and duties of the laity in church-life. Most of the community does not understand threefolds of Christ appropriately but they know differences between the duty the laity and threefolds of Christ exactly. Second, all of the PPC's members understand the meaning of the Pastoral Parish Council. Most of these PPC's members only understand the function and authority of PPC, however, most of these PPC fully understand the arrangement of the Pastoral Parish Council completely and a few number of the PPC's members only understands the four pastoral areas. Nevertheless, most of them understand the section of each four pastoral areas of PPC comprehensively. Third, some of the PPC's members ever served more than two periods. All of the PPC's members have motivation and spirit in PPC, but sometimes most of them fell lazy or not excited to participate. Fourth, all of the PPC's members propose and suggest to the people so that they have willing to participate in the Pastoral Parish Council and the pastoral work of the PPC.